Decomposing differences in the chronic disease condition between rural and urban older adults in China: a cross-sectional analysis - Zhang, Jian; Zhang, Yuan (Frontiers in Public Health, 2024)
Background: With the deepening of aging in China, there has been an increase in the older adults suffering from chronic diseases. However, there is little known about the differences in chronic disease condition between rural and urban older adults. The objective is to identify chronic disease condition and investigate the factors that cause differences in chronic disease condition between urban and rural older adults. Results: The study showed that the proportion of suffering from chronic diseases among urban older adults (51.26%) was significantly higher than that of rural older adults (46.56%). In suffering from chronic diseases, there were significant differences in gender, education level, minorities, religiosities, duration of sleep, drinking alcohol, social activity, insurance and socioeconomic status between rural and urban older adults; while in not suffering from chronic diseases, there were significant differences in age, education level, marital status, drinking alcohol, social activity, insurance, region and socioeconomic status between rural and urban older adults. For rural older adults, those who were widowers (Odds ratios (OR):1.267), drinking alcohol (OR:1.421) and had government medical insurance (OR:4.869), had higher odds of having chronic diseases. However, those were high school and above (OR:0.802), reporting duration of sleep 4 to 8 hours (OR:0.745) or above 8 hours (OR:0.649), had social activity (OR:0.778) and had the most affluent socioeconomic status (OR:0.778), had lower odds of having chronic diseases. As for urban older adults, those who were aged 65-74 years (OR:1.246) and had government medical insurance (OR:2.362) had higher odds of having chronic diseases. Fairlie’s decomposition analysis indicated 23.57% of the differences in suffering from chronic diseases could be traced to duration of sleep, drinking alcohol, social activity and region. Conclusions: This study illustrated that the proportion of chronic diseases was higher among urban older adults than rural older adults. Considering duration of sleep, drinking alcohol, region, social activity and region, the study demonstrated health differences between urban and rural older adults and provided evidence for policy-making to narrow the health gap between urban and rural areas.